2018
DOI: 10.1016/j.kjms.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Can endocan be a new biomarker in ventilator‐associated pneumonia?

Abstract: Ventilator‐Associated Pneumonia (VAP) is a hospital‐acquired bacterial infection with high incidence and mortality rate. The aim of this study is to investigate the correlation between the Endocan level and development of VAP and whether or not this correlation was correlated with the clinical findings. Demographic data, white blood cell (WBC) count, procalcitonin (PCT), c‐reactive protein (CRP), and fever levels of 60 patients were recorded in serial measurements for 5 days. When there was the presence of fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…17,18 It has been determined that serum endocan levels are increased in ventilator-associated pneumonia, which is an important cause of mortality in adult intensive care units. 19 All these studies supported the hypothesis of rapid release of endocan from the lung epithelium with other cytokines in the early stages of pneumonia.…”
Section: Discussionsupporting
confidence: 65%
“…17,18 It has been determined that serum endocan levels are increased in ventilator-associated pneumonia, which is an important cause of mortality in adult intensive care units. 19 All these studies supported the hypothesis of rapid release of endocan from the lung epithelium with other cytokines in the early stages of pneumonia.…”
Section: Discussionsupporting
confidence: 65%
“…The binding of ESM-1 to LFA1 inhibited the specific binding of ICAM-1 to Jurkat cells, implying that ESM1 could regulate LFA-1/ICAM-1 pathway and thus suppress lymphocyte recruitment to inflammatory sites and activation [19]. However, in vivo experiments and clinical data both supported that ESM1 promotes inflammatory and account for inflammatory related disease including ventilator associated pneumonia [28], cardiovascular disease [29], and sepsis [30]. By using Esm1 knockout mice Susana F. Rocha et al showed that Esm1 does not affect leukocyte rolling and adhesion in vivo, but positively regulates leukocyte extravasation at the endothelial transmigration level [31].…”
Section: Discussionmentioning
confidence: 99%
“…High endocan levels have been reported in patients with ventilator-associated pneumonia (VAP). Elevated endocan levels have been linked to the development of VAP, and that this can be used as a screening test ( 19 ). Another study reported increased serum endocan levels in severe sepsis patients requiring mechanical ventilation in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%